2013
DOI: 10.1051/limn/2013052
|View full text |Cite
|
Sign up to set email alerts
|

Internal nutrient loading may increase microcystin concentrations in freshwater lakes by promoting growth ofMicrocystispopulations

Abstract: -Nutrient release from lake sediments may increase concentrations of harmful algal toxins -such as microcystins -by stimulating blooms of toxigenic cyanobacteria. This hypothesis is supported by a series of experiments in which intact cores of sediment were incubated under different environmental conditions, after which the water overlying the sediments was harvested as a culture medium for growing a toxic strain of the common cyanobacterium Microcystis. Both littoral and profundal sediments from Lake Kinneret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…Eutrophication is widespread worldwide because of the coupled relationship between ever-growing human population and the concomitant increase in anthropogenic nutrient loading of aquatic ecosystems [1]. The increased nutrient (N and P) loading in overlying water promotes the growth of harmful algae and aggravates algal blooms [2,3]. These pose a threat to freshwater ecosystems and drinking water supplies because cyanobacteria synthesize toxic secondary metabolites, such as cyanotoxins [4].…”
Section: Introductionmentioning
confidence: 99%
“…Eutrophication is widespread worldwide because of the coupled relationship between ever-growing human population and the concomitant increase in anthropogenic nutrient loading of aquatic ecosystems [1]. The increased nutrient (N and P) loading in overlying water promotes the growth of harmful algae and aggravates algal blooms [2,3]. These pose a threat to freshwater ecosystems and drinking water supplies because cyanobacteria synthesize toxic secondary metabolites, such as cyanotoxins [4].…”
Section: Introductionmentioning
confidence: 99%
“…Sediment is often composed of nutrient-rich organic material as well as minerals deposited from surrounding rock formations. For example, Orihel et al demonstrated that nutrient release from lake sediments stimulated growth of a toxigenic strain of Microcystis, which in turn increased the concentrations of MCs [56]. MCs in sediments may also originate from multiple processes including growth or lysis of benthic cyanobacteria cells, adsorption of dissolved MCs to the sediment, and MCs bound in animal tissue or fecal matter post ingestion of MCs by benthic organisms [50].…”
Section: Detectionmentioning
confidence: 99%
“…The massive N and P accumulated in the sediments would release to the overlying water because of sediment resuspension, bioturbation, bacterial activity, redox conditions, oxygen saturation, and others (Hupfer and Lewandowski, 2008;Sndergaard et al, 2003). High internal N and P loadings have been proven to boost the growth of algae and aggravate the eutrophic status in many lakes (N¨urnberg et al, 2013;Orihel et al, 2013). Most of the eutrophic lakes around the world have high internal N and P loadings, such as Lake Taihu (Wang et al, 2017) and Lake Chaohu (Liu et al, 2015) in China, Lake Kinneret in Israel (Orihel et al, 2013), Lake Simcoe in Canada (N¨urnberg et al, 2013), and others.…”
Section: Introductionmentioning
confidence: 99%
“…High internal N and P loadings have been proven to boost the growth of algae and aggravate the eutrophic status in many lakes (N¨urnberg et al, 2013;Orihel et al, 2013). Most of the eutrophic lakes around the world have high internal N and P loadings, such as Lake Taihu (Wang et al, 2017) and Lake Chaohu (Liu et al, 2015) in China, Lake Kinneret in Israel (Orihel et al, 2013), Lake Simcoe in Canada (N¨urnberg et al, 2013), and others. The sediment-water interface (SWI) is the major place for the exchange of N and P between the sediment and the overlying water.…”
Section: Introductionmentioning
confidence: 99%